Criminal Responsibility for Perpetrators of the Crime of Distributing Illegal Beauty Products Without Permission from the Drug and Food Control Agency (Study Decision Number 418/Pid.Sus/2023/PN Tjk) - Safitri, Anggi; Jainah, Zainab Ompu; Ainita, Okta (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Beauty products that are illegal without a distribution license from the Food and Drug Administration may contain ingredients that are very harmful to the skin. Cosmetics according to the Minister of Health Regulation are materials used on the outside of the human body. One of the legal events regarding illegal beauty products without BPOM supervision as stipulated in the Tanjung Karang Class IA District Court Decision Number 418/Pid.Sus/2023/PN.Tjk. The problems in this study are what are the causal factors and reasons for the perpetrators to commit the crime of distribution of illegal beauty products without the Food and Drug Supervisory Agency and how the criminal liability of the perpetrators of the crime of distribution of illegal beauty products without the Food and Drug Supervisory Agency (Based on Decision Number 418/Pid.Sus/2023/PN Tjk). The research method used in this research is through normative juridical and empirical juridical approaches using secondary and primary data. Data collection is done by literature study and field study. The results of this thesis research can be concluded that the factors that cause the perpetrators to commit the crime of distributing illegal beauty products without the Food and Drug Administration are basically 2 factors. Namely the profit factor and the opportunity factor so that these circumstances force the defendant to commit the criminal act of distributing illegal beauty products. Then criminal liability for the perpetrator of distribution of illegal beauty products without the Food and Drug Administration (Based on decision number 418/Pid.Sus/2023/PN.Tjk), namely the defendant was secured by members of the BBPOM Bandar Lampung PPNS and then sentenced to imprisonment for 2 (Two) months minus the period of arrest and / or detention that has been served, and a fine of Rp. 10,000,000,00, - (ten million rupiah) subsidized by 1 (One) month of confinement as stated in decision number 418/Pid.Sus/2023 / PN.Tjk. Suggestions addressed by the author to law enforcement officials are expected to be able to improve their performance to overcome cases of illegal sales of beauty products containing hazardous ingredients quickly, and consider the use of legal instruments in the form of laws in accordance with the conditions of the case being handled and be more consistent and firm in applying legal provisions regarding cosmetics that do not have a distribution permit so that the application of sanctions is not different and not too light so that it can provide a deterrent effect to cosmetic business actors who do not have a distribution permit. Then the government should coordinate and cooperate with each other in eradicating the circulation of cosmetics without a distribution permit by applying the principles of coordination, integration and synchronization, especially the Food and Drug Supervisory Agency. In addition, it is expected that the public, especially women, should be more careful in choosing cosmetic products. Before buying a product, it would be nice to check the brand, expiration date, content, indications, and have been registered with BPOM.